234k views
0 votes
If you wanted to shift y=-3(x-2)^2+1 up4 and left2, what would be the new equation

User Rahul Modi
by
5.4k points

1 Answer

0 votes

Answer:

y = - 3x² + 5

Explanation:

The equation of a function is given by y = - 3(x - 2)² + 1 ...... (1)

Now, if we sift the graph of the above equation upward by 4 units, then y in the equation (1) shall be replaced by (y - 4)

Again, if we sift the graph of the above equation(1) towards left by 2 units, then x in the equation (1) shall be replaced by (x + 2)

Therefore, the final equation will be

(y - 4) = - 3(x + 2 - 2)² + 1

⇒ y = - 3x² + 5. (Answer)